EFFECT OF VITAMIN D SUPPLEMENTATION ON INSULIN SENSITIVITY AND ANDROGEN LEVEL IN VITAMIN D-DEFICIENT POLYCYSTIC OVARY SYNDROME PATIENTS - Al-thuwaynee, Saba M Swadi; Ahmed, Amaal Raad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: There is limited evidence that giving Vitamin D supplementation had a beneficial effect on insulin resistance and dysfunction of the menstrual cycle in females with polycystic ovary syndrome (PCOS). Thus, the aim of the present study is to evaluate the effect of Vitamin D supplementation on insulin sensitivity and androgen level in Iraqi females with PCOS. Methods: A randomized, blinded clinical trial design studied 60 Iraqi females with PCOS referring to the women's counseling, outpatients at maternity and pediatrics teaching hospital in AL-Qadisiyah city, Iraq, and private clinic. Non-probabilistic sampling involved women aged from 18 to 45 years established on inclusion criteria. The patients' basic data have been recorded. Then, we measured Vitamin D, testosterone level, and impaired glucose tolerance (IGT) test to all females. After the diagnosis of Vitamin D deficiency, Vitamin D was administering at 5000 units daily for 8 weeks. All data were remeasured after 2 months. Result: A total of 60 patients with polycystic syndrome enrolled in the study, age range from 18 to 39 years, mean age 27.48±5.95 years. The metabolic parameter have been checked at the beginning of the study, which include Vitamin D level 16.1±5.6, impaired glucose test reading 8.8±0.7 and testosterone level 4.5±0.64.. After 2 months of supplementation, there were 83.7% of patients reach the normal level of Vitamin D and 16.3% still had a low level of Vitamin D (p≤0.002) between two groups. In regard to IGT test after 2 months of supplementation, there were 51.6% of patients still who had impaired test while 48.4% reach the normal reading (p≤0.001). Conclusions: Women with PCOS have a statically significant low level of Vitamin D in mean, IGT test in the mean, and high level of testosterone, and there were inverse correlations between Vitamin D with IGT and testosterone.